The Life of the River Coastal Community and Folklore around the Kapuas River of Kapuas District of Sanggau Regency - Egi Pratama Rizqi; Arkanudin Arkanudin; Hasanah Hasanah (Balale' : Jurnal Antropologi, 2022)
This study discussed the topic of folklore that exists in society and the relevance of folklore which from time to time had been increasingly changing and changing its function and role in society making research on folklore that exists today very interesting to study. In modern society, the role of folklore was no longer the same as its role in the past. The life of coastal communities was the place where this research focused, looking at some of the folklore that exists in the lives of coastal communities in the Kapuas District of Sanggau Regency and examining how the relationship and influence of folklore and people's lives today. The results of this study showed that it turned out that folklore, which used to have several social roles in today's society in modern times, had played a small role, the occurrence of this was not only due to the development of science and technology as well as the tendency of logical thinking that existed in society, but also because of the generational change factor which finally broke the oral tradition in the spread of existing folklore. So folklore was only regarded as mere fairytale and myth and was almost seldom seen as its intrinsic value and meaning for social life.